ANALGESIC EFFECT OF INFUSA MIXTURE OF RED GINGER, TEMUKUNCI, KENCUR, LEMONGRASS AND TAMARIND ON FEMALE MICE BY WRITHING TEST METHOD. - Dani Sujana; Nurul; Dadang Muhammad Hasyim; Yogi Rahman Nugraha; Diah Wardani; Mina Pertiwi; Hesti Renggana (Pharma Xplore : Jurnal Sains dan Ilmu Farmasi, 2023)
Pain is an unpleasant sensory and emotional experience caused by actual or potential tissue damage. Based on systematic review studies it has been proven that red ginger, temukunci, kencur, lemongrass and tamarind have been shown to have analgesic effects both in vitro and in vivo. The purpose of this study was to determine the analgesic effect of IJTKSA. The method used in this study is a laboratory experiment with an analytical descriptive approach. The results showed that IJTKSA both concentrations of 0.02%, 0.04% and 0.08% were able to reduce the number of writhing mice. Overall, IJTKSA concentration of 0.02% has the most effective analgesic effect as evidenced by the low average total number of writhing mice during 60 minutes of observation.